The relationship of Grasha–Riechmann Teaching Styles with teaching experience of National-Type Chinese Primary Schools Mathematics Teacher - Sim, Sze Hui; Mohd Matore, Mohd Effendi Ewan (Frontiers in Psychology, 2022)
Grasha-Riechmann's Teaching Styles have a high potential to be applied in Mathematics specially to help increase teacher educators’ knowledge. However, very little attention has been paid to the study of identifying the teaching style patterns of Mathematics teachers at the primary school National-Type Chinese Primary Schools (SJKC). There is increasing concern about how this teaching style related to the teaching experience. This study aims to identify the patterns of Grasha-Riechmann Teaching Styles among primary school Mathematics teachers and the relationship between Grasha-Riechmann Teaching Styles with teaching experience. The quantitative approach through a survey was applied to 97 Mathematics teachers of SJKC Kepong, Kuala Lumpur using the simple random sampling method. The instrument was adapted from the Grasha-Riechmann Teaching Styles Questionnaire (1996), which measures five teaching styles such as Personal Model Teaching Style, Expert Teaching Style, Formal Authority Teaching Style, Delegator Teaching Style, and Facilitator Teaching Style. The patterns showed that the Personal Model Teaching Style is the most dominant, and the Facilitator Teaching Stie as the least dominant style. The Spearman’s Rho Correlation also reported a very weak significant correlation between Grasha-Riechmann Teaching Styles with the teachers’ Mathematics teaching experience, specifically for Expert, Formal Authority, and Facilitator Teaching Styles. The study provides practical implications for educators’ professional development to diversify the training of teachers by experience and adapt them to the needs of student learning in primary school. These findings trigger ideas to get a better understanding by another demographic variables such as gender, age and complexity of Mathematics subject.